Assessment of productivity and financial growth of credit cooperatives in the Visayas - Cinco, Jesus C., Jr (Danyag :the UPV journal of humanities and social sciences)
"This research determined the applicability of Dr. Jacqueline Doyle's Economies of Growth concept to the Philippine business environment, specifically credit cooperatives in the Visayas. Data from 1998 to 2002 was gathered using a combination of stratified sampling and judgment sampling approaches. Survey questionnaires were sent to VICTO-affiliated credit cooperatives located in the Visayas. Analysis of the data revealed that a) the economies of growth concept applies to institution as well as community-based credit cooperatives, and b) the results provide cooperative management with an empirical tool to assess their current performance in terms of Compound Annual Growth Rate (CAGR) of Core Business Human Resource Productivity (CBHRP) relative to their performance terms of CAGR Core Business Revenues or CAGR of Total Assets. Armed with this tool, a more scientific approach to benchmarking and forecasting strategic improvements in CAGR of CBHRP can be developed by cooperative management thereby contributing to the enhancement of organizational efficiency."